Effect of different irrigation activation systems using continuous chelating irrigation protocol on the removal of smear layer in the apical third of root canals: An in vitro scanning electron microscope study - Nikitha D'Souza; Ashwini Santhosh; Anitha Kumari; Chethana S Murthy; Vikram Gowda; Sudhanva Mallandur (Wolters Kluwer Medknow Publications, 2024)
Aim: Continuous chelation is a novel irrigation regimen popular as a single solution for irrigation of the root canal system during root canal therapy, especially for the removal of the smear layer. This study aimed to compare the effectiveness of three different irrigation activation systems in removing the smear layer from the apical third in single-rooted mandibular premolars using a scanning electron microscope (SEM). Methods: Fifty-six extracted single-rooted mandibular premolars were decoronated, and canals prepared till #30/0.09, with Chloroquick (3% NaOCl + 9% HEBP) as the working solution. Teeth were randomly divided into four groups based on the final irrigant activation protocol; Group A - (control group) conventional syringe irrigation with a 30-gauge single-side vented needle. Group B - (passive ultrasonic irrigation method) passive ultrasonic irrigation (PUI) with #20-Irrisafe ultrasonic files activated for 1 min. Group C - (sonic activation) EndoActivator system using the yellow tip (#20/0.04) activated for 1 min. Group D - Tornado Disinfection Kit using GF-brush for 20-30 s as per manufacturer's instructions. The canals were dried, samples were hemi-sectioned, and the amount of remaining smear layer was scored according to the Tabrizizadeh criteria (2015) with SEM images at ×2500 by two blinded operators. The collected data were analyzed statistically using the Chi-square test (P < 0.05). Results: The results showed statistically significant differences in terms of smear removal among the groups (P < 0.05) with the Gentlefile group performing better, followed by PUI, EndoActivator, and the conventional group. Conclusion: Within the limitations of the study, continuous chelation with Gentlefile activation could be a viable and efficient protocol for the removal of the smear layer from the apical third of root canals.